LINGUOCULTURAL AND STRUCTURAL-SEMANTIC FEATURES OF UZBEK AND ENGLISH TOPONYMS: A COMPARATIVE STUDY OF TERMEZ AND WINCHESTER PLACE NAMES (Multidisciplinary Journal of Science and Technology, 2026)
Toponyms function not only as geographical labels but also as linguocultural signs that preserve historical memory, collective identity, and semantic values of a speech community. This study provides a comparative analysis of Uzbek and English place names (toponyms) through the case of Termez (Uzbekistan) and Winchester (England). The research aims to identify structural-semantic patterns, etymological layers, and linguocultural meanings embedded in urban toponymic objects such as oikonyms, urbanonyms, hydronyms, and institutional names. Using descriptive, comparative, and linguocultural analytical methods, the study examines how language, culture, and history interact in the formation and functioning of toponyms. The findings reveal both universal and culture-specific tendencies: while English toponymy often exhibits morphologically transparent compound structures (e.g., Winchester), Uzbek toponymy reflects historical multilingual contact, metaphorical nomination, and culturally marked semantic motivation. The article argues that comparative toponymic studies offer a productive framework for understanding linguistic worldview differences and cultural conceptualizations across languages.